Engaging transgender women in HIV research in South Africa - L. Leigh Ann van der Merwe; Allanise Cloete; Helen Savva; Donald Skinner; Gita November; Zsa-Zsa Fisher (BMC Public Health, 2023)
Abstract The Botshelo Ba Trans study was the first HIV bio-behavioral survey conducted with transgender women in South Africa. Engaging research with marginalized communities requires clear points of entry, reference points for understanding the internal culture, and establishing trust and understanding. The community-based participatory research approach guided the development and implementation of this study. We conducted a rapid qualitative and pre-surveillance formative assessment between August 2017 to January 2018 and a bio-behavioral survey between July 2018 and March 2019. At the start, a Steering Committee, comprising primarily of transgender women, was established and subsequently provided substantial input into the mixed methods study conducted in Buffalo City, Cape Town, and Johannesburg. Key to the study's success was building trust and establishing ownership of the survey by transgender women recognized as expert knowledge holders. Thus, a community-based participatory research-informed approach enhanced the validity of the data and ensured that we addressed relevant issues.